Treatment and prognosis of spinal cord reperfusion injury after cervical spinal canal stenosis surgery: a case report - Diao, Wenbo; Yang, Jiankun; Hu, Ya-nan; Lou, Caili (Frontiers in Surgery, 2026)
BackgroundSpinal cord reperfusion injury of the cervical spine is a rare but severe postoperative complication, typically occurring after the decompression of chronically compressed spinal cord tissue. The report aims to present a case of early postoperative spinal cord reperfusion injury that was successfully managed, and to discuss its underlying pathogenesis, treatment strategies, and clinical outcomes.Case reportA 63-year-old middle-aged male was admitted with a 3-month history of neck and shoulder pain accompanied by numbness and pain in both upper limbs. MRI and clinical evaluations revealed cervical spinal canal stenosis with radiculopathy. The patient underwent anterior cervical discectomy and fusion (ACDF), with no intraoperative complications noted. 2 h after the operation, when the patient regained consciousness, it was found that the muscle strength of both lower limbs was grade 1, that of both upper limbs was grade 2, and the skin sensation of the lower limbs was gradually fades. However, four hours after surgery, upon regaining consciousness, the patient developed complete quadriplegia and loss of skin sensation, with progressive worsening. An emergency MRI ruled out intracranial pathology but revealed spinal cord edema at the surgical site. Based on the clinical course and imaging findings, spinal cord reperfusion injury was suspected. The patient was immediately transferred through the emergency “green channel” for urgent posterior cervical laminoplasty to achieve expanded decompression, accompanied by intraoperative and postoperative high-dose corticosteroid therapy. One day after the second surgery, the patient's muscle strength improved to Grade 3. Following two months of postoperative treatment and rehabilitation, the patient made a full recovery and was discharged. Follow-up MRI demonstrated substantial resolution of spinal cord edema and restoration of spinal cord morphology. This case illustrates that early recognition of spinal cord reperfusion injury and timely, appropriate intervention can significantly improve neurological outcomes, providing valuable insight for the management of similar cases.ConclusionSpinal cord reperfusion injury after cervical spine surgery is rare, but once it occurs, it requires a high level of clinical vigilance. Identifying the underlying cause, making a rapid diagnosis, and initiating timely surgical intervention combined with corticosteroid pulse therapy are essential to preventing irreversible neurological damage.